Program to Increase Literacy Understanding of Islamic Religion in Payadapur Village, East Kluet District, Nanggroe Aceh Darussalam - Ahmad Zaky; Bagas Pranomo; Ahmad Sholihin; Andika Permana Lubis; Habib Raihan Lubis; Radya Fauzan Nasution; Tangguh Putera Perdana; Rydan Alpin Putra (ASSUNNAH PRESS, 2024)
This research is research carried out in the community service program carried out by KKNT STAI As-Sunnah Lecturers and Students with programs to increase literacy for understanding the Islamic religion towards society. It is very important to implement it because of the importance of strengthening literacy in the Islamic religion. Religious literacy helps someone understand the principles -the basic principles of their religion, including religious beliefs, doctrines, and practices. This research aims to assist in developing a deeper understanding of religious teachings and how to apply them in everyday life. This research uses the PAR Participatory Action Research method, PAR is an approach whose process aims at learning in overcoming problems and meeting the practical needs of society, as well as the production of knowledge and processes. socio-religious change and Strengthening Religious Identity. Understanding religion well can strengthen a person's religious identity. Thus, religious literacy plays an important role in the formation of individuals who are tolerant, educated and empowered in a social and spiritual context. This Religious Literacy Program practically needs to be implemented, because of the lack of attention from stakeholders towards the community, especially towards understanding and knowledge of the Islamic religion of the community itself.